Recommendations and guidance for providing pharmaceutical care services during COVID-19 pandemic: A China perspective - Zheng, Si-qian (Res Social Adm Pharm, 2021)
BACKGROUND: The novel coronavirus pneumonia (COVID-19), which was first detected in Wuhan City, has now became a pandemic that affecting patients around the world. Particularly, the community patient population are at high risk of infection and are facing potential failure of proper medication use during the pandemic. OBJECTIVE: To discuss community pharmacists’ role and the content of pharmaceutical care (PC) during the novel coronavirus pandemic to promote effective prevention and control and safe drug use of the community patient population. METHOD: Collect and summarize the experience Chinese community pharmacies gained from providing pharmacy services during the COVID-19 outbreak, and taking patients' PC needs into consideration, analyze and discuss the methods and strategies that community pharmacies and pharmacists shall use to provide PC during the pandemic. RESULTS: Community pharmacy management teams shall support PC services by providing adequate supply of COVID-19 related medications and preventative products, following environment regulations, and providing sufficient staff trainings. Pharmacists shall use various approaches to provide PC services in drug dispensing, consulting and referrals, chronic disease management, safe use of infusions, patient education, home care guidance and psychological support to promote the COVID-19 pandemic control and ensure safe medication use of community patients during the pandemic. CONCLUSION: PC services in communities during the COVID-19 shall possess different properties due to disease characteristics and related change in patients' need. Community pharmacies shall work as a strong supporter of patient's medication and protective equipment supply. Community pharmacists shall be prepared to provide skilled and effective PC services for community patient population to ensure medication safety and promote the overall COVID-19 pandemic control.